Determinants of anemia in women of reproductive age in Indonesia: Secondary data analysis of the 2018 Indonesia Basic Health Research - Putu Sri Utami; Luh Seri Ani; Dinar Saurmauli Lubis; Dewa Nyoman Wirawan (Universitas Udayana, 2020)
Background and purpose: Anemia in women is a public health concern that is prevalent in developing countries. Women of reproductive age (WRA) frequently suffer from anemia, which can contribute to morbidity and mortality of mothers and their infants. The purpose of this study was to determine the prevalence and factors associated with anemia among women of reproductive age (WRA) in Indonesia. Methods: This study uses secondary data from the 2018 Indonesia Basic Health Research or Riset Kesehatan Dasar (Riskesdas) which was conducted in 34 provinces in Indonesia. The number of samples analyzed was 3,677 women aged 15-49 years who had data from interviews, measurements of height, weight, results of malaria tests, and hemoglobin levels. Data analysis was performed using multivariate logistic regression to determine the relationship between anemia and individual characteristics, nutritional and health status as well as environmental conditions and healthservice accessibility. Results: The prevalence of anemia among WRA in Indonesia was 25.3% (95%CI: 23.9-26.7). Factors which found to be associated with the prevalence of anemia in WRA were age <20 years (AOR=3.44; 95%CI: 2.22-5.35; p<0.001), underweight (AOR=1.48;95%CI: 1.08-2.05; p=0.017), obesity (AOR=0.68; 95%CI: 0.56-0.81; p<0.001) and the use of hormonal contraception (AOR=0.53;95%CI: 0.44-0.64; p<0.001). Conclusion: Based on the prevalence, anemia among WRA inIndonesia is categorized as a moderate public health concern and the most common risk factor for anemia was WRA aged <20 years and underweight. To reduce the incidence of anemia in WRA, interventions should be targeted at WRA aged <20 years and underweight